Eurokrisen og EU: Fra utilstrækkelige strategier til problematisk føderalisering? - Kelstrup, Morten (Politik, 2013)
The so-called ‘Eurocrisis’ consists of a complicated pattern of di erent economic and political crises. e article identi es some of the most important of these and attempts to characterize EU’s answers to them. It concludes that EU’s present priority to a legal-administrative strategy of budget control which economically implies a policy of austerity also as answer to depression, is clearly insu cient, and that EU’s present plans for a federalization of the Eurozone which can be seen as a continuation of the legal-administrative strategy of budget control, is going to create new problems if it is implemented.